Are increased frequency of macrophage-like and natural killer (NK) cells, together with high levels of NKT and CD4(+)CD25(high) T cells balancing activated CD8(+) T cells, the key to control Chagas’ disease morbidity? - Vitelli-Avelar, D M (Blackwell Science Inc, 2006)
The immunological response during early human Trypanosoma cruzi infection is not completely understood, despite its role in driving the development of distinct clinical manifestations of chronic infection. Herein we report the results of a descriptive flow cytometric immunophenotyping investigation of major and minor peripheral blood leucocyte subpopulations in T. cruzi-infected children, characterizing the early stages of the indeterminate clinical form of Chagas’ disease. Our results indicated significant alterations by comparison with uninfected children, including increased values of pre-natural killer (NK)-cells (CD3(–) CD16(+) CD56(–)), and higher values of proinflammatory monocytes (CD14(+) CD16(+) HLA-DR(++)). The higher values of activated B lymphocytes (CD19(+) CD23(+)) contrasted with impaired T cell activation, indicated by lower values of CD4(+) CD38(+) and CD4(+) HLA-DR(+) lymphocytes, a lower frequency of CD8(+) CD38(+) and CD8(+) HLA-DR(+) cells; a decreased frequency of CD4(+) CD25(HIGH) regulatory T cells was also observed. These findings reinforce the hypothesis that simultaneous activation of innate and adaptive immunity mechanisms in addition to suppression of adaptive cellular immune response occur during early events of Chagas’ disease. Comparative cross-sectional analysis of these immunophenotypes with those exhibited by patients with late chronic indeterminate and cardiac forms of disease suggested that a shift toward high values of macrophage-like cells extended to basal levels of proinflammatory monocytes as well as high values of mature NK cells, NKT and regulatory T cells, may account for limited tissue damage during chronic infection favouring the establishment/maintenance of a lifelong indeterminate clinical form of the disease. On the other hand, development of an adaptive cell-mediated inflammatory immunoprofile characterized by high levels of activated CD8(+) cells and basal levels of mature NK cells, NKT and CD4(+) CD25(HIGH) cells might lead to late chronic pathologies associated with chagasic heart disease.